Evaluasi Kebijakan Layanan Online dalam Meningkatkan Pengelolaan Data Kesejahteraan Masyarakat pada Dinas Sosial Kabupaten Buol - Satria Satria (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2026)
Digital transformation has become an essential strategy for improving the effectiveness, transparency, and accountability of public service delivery. However, community welfare data management continues to face several challenges, including inaccurate data, limited technological infrastructure, and low levels of digital literacy. Although previous studies have discussed digital public services, evaluations of online service policies for community welfare data management at the Social Service Office of Buol Regency remain limited. This study aims to evaluate the online service policy and identify the challenges affecting its implementation. A qualitative descriptive approach was employed using interviews, observations, and documentation involving officials of the Social Service Office, online service operators, data management officers, and community members. Data were analyzed through data reduction, data display, and conclusion drawing based on William N. Dunn's policy evaluation model. The findings indicate that the online service policy has improved the effectiveness, efficiency, adequacy, responsiveness, and appropriateness of community welfare data management. However, the equity dimension remains suboptimal due to limited technological infrastructure, low digital literacy, dependence on manual verification, and limited human resources. This study contributes to the literature on digital public service policy evaluation and provides practical recommendations for optimizing community welfare data management.